(untitled) - Di Stefano, Michael (Hoboken, N.J., 2005)
With technology budgets under increasing scrutiny and system architecture becoming more and more complex, many organizations are rethinking how they manage and use technology. Keeping a strong business focus, this publication clearly demonstrates that the current ways of tying applications to dedicated hardware are no longer viable in today's competitive, bottom line-oriented environment. This evolution in distributed computing is leading a paradigm shift in leveraging widely distributed architectures to get the most processing power per IT dollar. Presenting a solid foundation of data management issues and techniques, this practical book delves into grid architecture, services, practices, and much more, including: Why businesses should adopt grid computing; How to master the fundamental concepts and programming techniques and apply them successfully to reach objectives; How to maximize the value of existing IT investments. The author has tailored this publication for two distinct audiences. Business professionals will gain a better understanding of how grid computing improves productivity and performance, what impact it can have on their organization's bottom line, and the technical foundations necessary to discuss grid computing with their IT colleagues. Following the author's expert guidance and practical examples, IT professionals, architects, and developers will be equipped to initiate and carry out successful grid computing projects within their own organizations.
Keywords: Mạng máy tính ( hệ thống mạng ),Quản trị cơ sở dữ liệu,Computational grids (Computer systems),Database management